Development of a web-based financial application system - Hasan, M R; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Ferdaus, M M; Khan, M N H; Mostafa, M G (IOP Publishing, 2013)
The paper describes a technique to develop a web based financial system, following latest technology and business needs. In the development of web based application, the user friendliness and technology both are very important . It is used ASP .NET MVC 4 platform and SQL 2008 server for development of web based financial system. It shows the technique for the entry system and report monitoring of the application is user friendly. This paper also highlights the critical situations of development, which will help to develop the quality product